THE QUALITY OF MODEL WRITTEN TEXTS IN THE RECOMMENDED SENIOR HIGH SCHOOL ENGLISH TEXTBOOK. - Rukmini, Dwi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Abstract The article is written based on the study on the model written texts provided in the Senior High School (SHS) English textbooks. It is aimed at finding out the quality of model written texts available in the textbooks for SHS students. The method of the study is discourse analysis, and the approach is qualitative. The data are 115 reading texts provided in the six recommended English textbooks published by six different publishers. The units of analysis are text and clause. The instrument for analyzing the realization is the three strands of meanings that a clause can encode, which is suggested by Halliday (1994). The results reveal that only eleven out of a hundred and fifteen reading texts are problematic in their rhetorical developments. This indicates that most of them achieve their respective social purposes and can be used as model texts. In terms of the rhetorical development realization, ten out of eleven reading texts are problematic. Therefore they fail to achieve their social purposes. It can be concluded that 90.43 % have good quality meaning that they are written based on the required conventions of genre writing suggested by English community.